1996
DOI: 10.1073/pnas.93.12.5985
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-bound agrin induces expression of acetylcholine receptor epsilon-subunit gene in cultured mammalian muscle cells.

Abstract: Expression of the e-subunit gene of the acetylcholine receptor (AChR) by myonuclei located at the neuromuscular junction is precisely regulated during development. A key role in this regulation is played by the synaptic portion of the basal lamina, a structure that is also known to contain agrin, a component responsible for the formation of postsynaptic specializations. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 35 publications
3
79
1
Order By: Relevance
“…These increases are in fact of similar magnitude to those reported recently by Jones et al (45) who examined the impact of both muscle and neural isoforms of agrin on expression of transcripts encoding the AChR ⑀-subunit. However, a major difference between the two studies is that we were able to observe an effect on utrophin gene expression without the necessity of agrin being substrate-bound (45). Although the reason for this difference remains currently obscure, it appears reasonable to assume that it likely arises from differences in culture conditions.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…These increases are in fact of similar magnitude to those reported recently by Jones et al (45) who examined the impact of both muscle and neural isoforms of agrin on expression of transcripts encoding the AChR ⑀-subunit. However, a major difference between the two studies is that we were able to observe an effect on utrophin gene expression without the necessity of agrin being substrate-bound (45). Although the reason for this difference remains currently obscure, it appears reasonable to assume that it likely arises from differences in culture conditions.…”
Section: Discussioncontrasting
confidence: 41%
“…In particular, recent experiments have revealed that Matrigel TM is capable of binding agrin (46,47). Since, in our experiments, myotube cultures are plated on Matrigel-coated plates, it appears likely that Torpedo agrin as well as recombinant agrin fragments may become bound to this substrate via an unknown mechanism (see Denzer et al (46,47) for further discussion) and therefore do not remain in a "soluble" form (45). Nonetheless, since the pattern of expression of the utrophin gene along muscle fibers resembles that of the ⑀-subunit gene (26,36,48), these results are coherent with the notion that expression of genes encoding membrane and cytoskeletal proteins of the postsynaptic membrane are co-regulated and therefore involve a common signal transduction pathway.…”
Section: Discussionmentioning
confidence: 98%
“…The dependence of Na ϩ channel aggregation on agrin immobilization also may explain apparently conflicting re- sults by Corfas and Fischbach (1993) that Na ϩ channels in cultured chick myotubes are induced by ARIA / heregulin, but not by soluble agrin. As proposed here and previously (Jones et al, 1996(Jones et al, , 1997 for agrin-induced AChR gene expression, agrin attached to BL may stimulate the muscle fiber to secrete neuregulin and /or modif y the BL in such a way as to provide binding sites for muscle-derived N RG. Such N RG aggregates would, in turn, induce the ectopic Na ϩ channel aggregates.…”
Section: Accumulation Of Na ؉ Channels and The Formation Of Ectopic Jmentioning
confidence: 98%
“…By inducing ectopic secretion of neural agrin from muscle fibers in vitro and in vivo, we have shown recently that neural agrin, immobilized presumably by attachment to the extracellular matrix, is sufficient to induce ectopic adult-type AChR aggregates (Jones et al, 1996(Jones et al, , 1997. Given the functional similarities of ectopic agrin-induced AChR clusters to AChRs at normal mature endplate membrane, we now show that the neural agrin isoform cAgrin 7A4B8 also induces the localized expression of structural components characteristic of a normal postsynaptic apparatus.…”
mentioning
confidence: 96%
See 1 more Smart Citation